Foundation Expression Blend 2 building applications in WPF and Silverlight - Gaudioso, Victor; SpringerLink (Online service) (Berkeley, CA : Apress, Inc., 2008)
Provides information on using Blend to design media applications, Web-based animations, and games.
Includes index.
Includes bibliographical references and index.
Keywords: Web sites -- Authoring programs; Web sites -- Design; Multimedia systems; Internet programming